COMPARISON OF ACE INHIBITOR (FOSINOPRIL) AND Β-ADRENOBLOCKER (ATENOLOL) EFFECTS ON AUTONOMIC REGULATION OF THE HEART IN PATIENTS WITH ARTERIAL HYPERTENSION - A. R. Kiselyov; V. I. Gridnev; O. V. Shevchenko; O. M. Posnenkova; A. N. Strunina; V. A. Schwarz; Ja. P. Dovgalevsky (Столичная издательская компания, 2016)
Aim. To estimate effects of fosinopril and atenolol on autonomic regulation of heart in patients with arterial hypertension (HT) on the basis of spectral characteristics of heart rate variability (HRV).Material and methods. 49 patients (46±7 y.o.) with untreated or inadequately treated HT without end organ damages and associated clinical conditions were involved in the study. Heart rhythm was registered during passive orthostatic test with spontaneous breath within 10 min for each stage of the test. HRV was estimated by parametrical method based on autoregression model. Frequency power of HRV spectrum (ms2 ) in high-frequency (HF: 0,15-0,4 Hz) and low-frequency (LF: 0,04-0,15 Hz) ranges was calculated as well as the total power of a spectrum (ТР).Results. Fosinopril and atenolol reduced in blood pressure levels similarly, atenolol as well reduced in heart rate. Fosinopril and atenolol changed power of LF-range in comparable decreasing manner in upright position. Fosinopril therapy resulted in the same changes with power of HF-range. Atenolol increased power of HF-range in horizontal position and had no effect in upright position. There were not dynamic in TP during treatments.Conclusion. Fosinopril and atenolol have similar effects on the central mechanisms of autonomic heart regulation and HRV, though atenolol effect on sympathetic-parasympathetic balance is more prominent.